How fighter pilots use math - Hense, Mary. (New York : Chelsea Clubhouse, 2010)
Photographs, illustrations, and charts describe how fighter pilots use math in order to complete their missions.
Includes bibliographical references (p. 31) and index.
6.0
3-6
3-6
Keywords: Aeronautics -- Mathematics -- Juvenile literature; Fighter pilots -- Juvenile literature; Mathematics -- Juvenile literature; Aeronautics -- Mathematics; Fighter pilots; Mathematics; Aeronautics -- Mathematics; Fighter pilots; Mathematics